Protocolos a aplicar en la forensia informática en el marco de las nuevas tecnologías (pericia – forensia y cibercrimen) - Piccirilli, Darío (2016)
Esta Tesis intenta realizar una serie de aportes sobre la Forensia en Informática, contemplando las nuevas tecnologías que hoy día aplican en los procesos judiciales y que derivan en Pericias muy específicas y complicadas, tareas técnicas sobre las que no se puede generar ninguna duda en el tratamiento de la prueba. Es decir, el proceso de generación de la prueba, desde el secuestro de la misma hasta el análisis pericial, debe ser indubitable, de manera tal que quien deba impartir justicia pueda contar con elementos claros, contundentes y útiles. La informática puede considerarse que se encuentra relacionada en forma transversal con gran parte de la problemática judicial, aplicando en los distintos fueros de la Justicia Argentina, tanto en lo Laboral, Comercial, Civil, Contencioso Administrativo Federal, Penal Económico, Criminal y también para la Corte Suprema.The process of generation of proof can consist of many stages, depending on the situation in which the computer expert can intervene. In other words, it is fundamental to understand the situation in which proof can or must be collected. During a search and seizure (the moment in which equipment is seized or information is “collected”, avoiding the seizure of critical equipment for the organization searched), information that has already been seized may have to be analysed, or it may have to be obtained on the basis of data seized from optical or magnetic storage media. These processes must follow best practices, applying work protocols accepted worldwide and employing trustworthy tools. Information obtained as digital evidence for the trial must be indubitable, so that the Court that must impart justice can count on elements that are clear, forceful and useful. Although this applies to Criminal law in Argentina, it is important to comprehend these practices and procedures in order to extrapolate the collection of digital evidence to other aspects of the Law, where, although there may be no procedure such as search and seize, a previous process, understood as a “pre proof” of digital evidence, may occur. This procedure may apply to Labour, Commercial and Civil law.Facultad de Informátic